2021
DOI: 10.3390/ijerph18189884
|View full text |Cite
|
Sign up to set email alerts
|

“Medical Student Syndrome”—A Myth or a Real Disease Entity? Cross-Sectional Study of Medical Students of the Medical University of Silesia in Katowice, Poland

Abstract: The description of Medical Student Syndrome is based on the assumption that inexperienced medical students are prone to develop a pathological fear of medical conditions they are taught about. The aim of this study is to examine the sample of students (medical and non-medical) in order to assess and compare their level of hypochondriacal attitudes and health-related anxiety. We also examined other factors which might have had an influence on hypochondria and nosophobia attitudes among students. Methods: The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
(45 reference statements)
0
12
0
Order By: Relevance
“…Moreover, after the outbreak of COVID-19, 11 out of 14 studies reported that medical students had better or similar mental health status in China, Poland, France, Saudi Arabia, and Turkey, when compared with non-medical students [ 49 , 66–75 ], which was in line with our study. Only three studies showed a significantly higher level of depression symptoms, anxiety symptoms, and stress among medical students [ 63 , 76 , 77 ]. Taken together, the above findings might suggest that medical students were not at a higher risk of mental distress compared with their peers in non-medical majors.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, after the outbreak of COVID-19, 11 out of 14 studies reported that medical students had better or similar mental health status in China, Poland, France, Saudi Arabia, and Turkey, when compared with non-medical students [ 49 , 66–75 ], which was in line with our study. Only three studies showed a significantly higher level of depression symptoms, anxiety symptoms, and stress among medical students [ 63 , 76 , 77 ]. Taken together, the above findings might suggest that medical students were not at a higher risk of mental distress compared with their peers in non-medical majors.…”
Section: Discussionmentioning
confidence: 99%
“…But non-medical universities in Katowice, shows that the percentage showing susceptibility to hypochondria and nosophobia symptoms are high compare to the students of medicine. 9 But our present study shows that the medical students i.e., nursing students are more susceptible to hypochondrial attitude. A cross sectional study was conducted to assess increased frequency of health anxiety in health science students and non-health science students in a Greek university.…”
Section: Discussionmentioning
confidence: 44%
“…This is similar to a more established notion of "medical student syndrome", where medical students develop symptoms that relate to the diseases they are studying [14]. Although research about the mental health aspect of the medical student syndrome remains to be evaluated [15], a serious concern was raised [16]. Indeed, the medical students' syndrome-medical students falsely relate themselves with a health condition that they are learning, impacting their health negatively [14]-may apply to the mental health contexts too.…”
Section: Introductionmentioning
confidence: 67%